Optimization of maternal and child health services based on digital systems for stunting prevention - Hendra Yulita; Sultina Sarita; Wahida Wahida (Indonesian Institute For Counseling, Education and Therapy, 2026)
Stunting remains a major public health challenge in Indonesia due to its long-term consequences on physical growth, cognitive development, and future productivity. Optimizing maternal and child health services is therefore essential to strengthen stunting prevention efforts. This study aimed to explore the implementation of digital-based maternal and child healthcare services and identify strategies for optimizing their role in stunting prevention. A qualitative descriptive design was employed in Kendari City, Indonesia. Fifteen participants, including midwives, nutrition officers, Posyandu cadres, and maternal and child health program coordinators, were selected through purposive sampling based on their direct involvement in maternal and child health services and experience with digital health applications. Data collection was conducted through semi-structured interviews and document reviews and continued until sufficient thematic depth was achieved across participant groups. Data were analyzed using thematic analysis involving coding, categorization, and theme development. To enhance trustworthiness, source triangulation and member checking were applied throughout the study. The findings revealed six major themes. Digital health systems were perceived to improve service quality through faster reporting, more accurate health records, real-time monitoring, enhanced maternal health literacy, and strengthened early detection of stunting risks. Digital platforms also expanded access to healthcare information and services. However, implementation barriers included unstable internet connectivity, limited digital infrastructure, variations in digital literacy, and fragmented information systems. The study suggests that integrated digital health systems may strengthen maternal and child healthcare services and support stunting prevention efforts, although implementation success depends on infrastructure readiness, workforce capacity, and system integration.